Pementasan Musik Genggong di Desa Batuan Kabupaten Gianyar : (Perspektif Pendidikan Agama Hindu) - Saputra, I Kadek Bharata Dwyq; Temon Astawa, I Nyoman; Sukerni, Ni Made (Metta : Jurnal Ilmu Multidisiplin, 2023)
Bali is known for its arts, culture, and traditions because every tradition and culture is always based on Hinduism and does not leave the local culture that already exists in the area. One of them is the performance of genggong music in Batuan Village, Sukawati District, Gianyar Regency. This study aimed to determine: (1) the form of genggong music performance in Batuan Village, Sukawati District, Gianyar Regency. (2) The function of Genggong Music Performance in Batuan Village, Sukawati District, Gianyar Regency. (3) The values of Hindu religious education are contained in the genggong music performance in Batuan Village, Sukawati District, Gianyar Regency. The method used to collect data is observation, interviews, documentation, and literature study. The data analysis technique in this study was through three stages, namely descriptive, data reduction, and conclusion drawing. The result shows: (1) there are several stages in playing genggong music, playing techniques, the duties of each instrument and the composition of the musicians in genggong music performances. (2) The functions of genggong music performance in Batuan Village, Sukawati District, Gianyar Regency, namely social functions, aesthetic functions, expressive functions, and cultural preservation. (3) The value of Hindu religious education contained in the genggong music performance in Batuan Village, Sukawati District, Gianyar Regency, namely the value of religious education, the value of ethical education (morals), the value of event education, the value of social education and cultural values. Based on the results of the study, it can be concluded that the genggong music performance is the work of the "pengangon” (shepherd). On the other hand, some say that the term genggong comes from the sound produced by the instrument when it is exhaled. The sound produced from these gusts is “ngeng” and “ngoring” so the instrument is named genggong.